Leaving Prostitution : Getting Out and Staying Out of Sex Work - Oselin, Sharon S. (Book collections on Project MUSE., 2014)
While street prostitutes comprise only a small minority of sex workers, they have the highest rates of physical and sexual abuse, arrest and incarceration, drug addiction, and stigmatization, which stem from both their public visibility and their dangerous work settings. Exiting the trade can be a daunting task for street prostitutes; despite this, many do try at some point to leave sex work behind. Focusing on four different organizations based in Chicago, Minneapolis, Los Angeles, and Hartford that help prostitutes get off the streets, Sharon S. Oselin's Leaving Prostitution explores the d.